The Importance of Marbles in Science Education for Elementary School Children - Kreinsen , Jens J. (Assyfa Learning Journal, 2024)
Rendahnya keterampilan berbicara bahasa Indonesia siswa disebabkan oleh kurang optimalnya guru dalam menggunakan dan menerapkan model pembelajaran dan media pembelajaran dalam proses pembelajaran, sehingga menyebabkan siswa kurang terampil dalam kegiatan berbicara. Saat kegiatan pembelajaran berlangsung baik diskusi kelompok maupun diskusi kelas, pembelajaran terkesan pasif. Siswa lemah dalam mengemukakan pendapat dengan baik dalam proses bertanya maupun proses menjawab pertanyaan. Oleh karena itu, penelitian ini bertujuan untuk membantu meningkatkan keterampilan berbicara siswa dengan menggunakan model pembelajaran word square dan media mystery board. Perlu dikembangkan dan diterapkan model pembelajaran dan media pembelajaran yang sesuai dengan kondisi kelas dan kebutuhan siswa untuk memfasilitasi proses pembelajaran secara aktif dan efektif, agar mampu menciptakan suasana kelas dan proses pembelajaran yang lebih hidup, kreatif, cermat dan menarik. Diharapkan pula siswa lebih aktif dalam mengemukakan pendapat baik berupa pertanyaan, saran, tanggapan maupun kritik saat kegiatan pembelajaran berlangsung, sehingga penggunaan model pembelajaran dan media pembelajaran yang tepat dapat membantu peningkatan keterampilan berbicara bahasa Indonesia yang baik dan benar.This study explores the effectiveness of educational marbles in increasing the understanding of science concepts in elementary school students in Germany. Using the quasi-experimental approach, 80 elementary school students in Germany are divided into two groups: control groups who use traditional methods and experimental groups that use educational marbles. The marbles used have been culturally adapted for the German context and are specifically designed to support learning science concepts. Increased understanding of science concepts is measured through initial tests and final tests and analyzed using inferential statistical analysis. The results showed that the experimental group experienced a significant increase in understanding the concept of science compared to the control group. For example, the average score of the final test of the experimental group increased from 65 to 85 (p <0.05), while the control group only increased from 64 to 70 (p> 0.05). This finding shows that the game of educational marbles can make learning more interactive and interesting, as well as increase understanding of science concepts in elementary school students. In addition, this research highlights the importance of adaptation of local culture in the development of teaching materials. The marble is used to integrate the elements of German culture, which helps students feel more connected with learning materials. However, this research also found that students with certain motor difficulties face greater challenges in using this game. For example, students with limitations in hand-eye coordination have difficulty controlling marbles, which affects their participation in learning activities. Overall, this research suggests the use of educational games in teaching science to create a more interactive and fun learning environment. The results of this study support further development of culturally adapted educational games to increase the effectiveness of learning in various contexts of education.